Beyond "yesterday's tomorrow": future-focused mobile interaction design by and for emergent users. (February 2017) - Jones, Matt; Robinson, Simon; Pearson, Jennifer; Joshi, Manjiri; Raju, Dani; Mbogo, Charity; Wangari, Sharon; Joshi, Anirudha; Cutrell, Edward; Harper, Richard
Abstract Mobile and ubiquitous computing researchers have long envisioned future worlds for users indeveloped regions. Steered by such visions, they have innovated devices and services exploring the value of alternative propositions with and for individuals, groups and communities. Meanwhile, such radical and long-term explorations are uncommon for what have been termed emergent users; users, that is, for whom advanced technologies are just within grasp. Rather, a driving assumption is that today's high-end mobile technologies will "trickle down" to these user groups in due course. In this paper, we open the debate about what mobile technologies might be like if emergent users were directly involved in creating their visions for the future 5–10 years from now. To do this, we report on a set of envisioning workshops in India, South Africa and Kenya that provide a roadmap for valued, effective devices and services for these regions in the next decade.